The Juridical Implication on Signature of a Notary or Official Land Deed on the Statement Certificate of Transfer of Rights of a Land and/ or Building or the Amendment of Bonding Agreement of Sale and Purchase of Land and/ or Building - Sumawati Sumawati; Tunggal Anshari Setia Negara; R Imam Rahmat Safi’i (Unram Law Review, 2019)
This research journal discusses legal issues relating to the legal implications of Notary Public or Land Deed Officials (PPAT) in the declaration of transfer of land and / or building rights or the amendment of sale and purchase agreement on land and building to be reviewed from Appendix II of the Regulation of the General Director of Tax No. PER-18 / PJ / 2017. Based on Article 3 of the Regulation of General Director of Tax Number PER-18 / PJ / 2017 concerning Procedures of Research of Proof of Fulfillment of Tax Obligation of Income Tax on Transfer of Right to Land and / or Building and Sale and Purchase Agreement on land and / or building and its amendment, where the taxpayer or his / her proxy is required to submit a research request proof of the fulfillment of the obligation to deposit the income tax one of them by attaching the Statement of transfer of rights to the land and or building that has been filled completely and stamped, and a copy of proof of sale and / or receipt of cash in cash which has been signed by the party that transferred the right to the land. Therefore, the Notary or Officer of the Deed of Land (PPAT) as the official authorized to make the deed related to the transfer of land and / or building rights are required to participate in knowing and signing the Statement of Transfer of Land and / or Land Rights. Pursuant to this matter, this research aims to know and analyze authority and responsibility of Notary / PPAT in signing letter of transfer of right of land and / or building, and juridical implication of Notary / PPAT signature in the statement letter. The research method used by the writer is the statutory approach. Notary / PPAT does not need to be involved in the Letter of Declaration of the transfer of land and building rights, and the Notary Law does not mention any applicable sanctions.